2010
DOI: 10.5483/bmbrep.2010.43.5.349
|View full text |Cite
|
Sign up to set email alerts
|

OIP5 is a highly expressed potential therapeutic target for colorectal and gastric cancers

Abstract: Previously, we reported that overexpression of Opa (Neisseria gonorrhoeae opacity-associated)-interacting protein 5 (OIP5) caused multi-septa formation and growth defects, both of which are considered cancer-related phenotypes. To evaluate OIP5 as a possible cancer therapeutic target, we examined its expression level in 66 colorectal cancer patients. OIP5 was upregulated about 3.7-fold in tumors and over 2-fold in 58 out of 66 colorectal cancer patients. Knockdown of OIP5 expression by small interfering RNA sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 21 publications
(11 reference statements)
1
25
0
Order By: Relevance
“…These results suggest that OIP5 expression is correlated with the mitotic proliferation of tumor cells, and that OIP5 knockdown-mediated inhibition of tumor cell growth causes accumulation of G 2 /M phase cell cycle regulators via OIP5/AKT signaling. Interestingly, our data also demonstrated that OIP5 knockdown induced apoptotic cell death, as reported previously [23]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggest that OIP5 expression is correlated with the mitotic proliferation of tumor cells, and that OIP5 knockdown-mediated inhibition of tumor cell growth causes accumulation of G 2 /M phase cell cycle regulators via OIP5/AKT signaling. Interestingly, our data also demonstrated that OIP5 knockdown induced apoptotic cell death, as reported previously [23]. …”
Section: Discussionsupporting
confidence: 91%
“…In addition, transient expression of OIP5 in NIH3T3 cells results in an increase in proliferation rate, highlighting its oncogenic properties [5]. Recently, OIP5 has also been reported to be upregulated in the tumors of colorectal cancer patients [6] and in female acute myeloid leukemia patients [7], implicating the protein as a potential therapeutic target for cancer [8]. Furthermore, it is a promising target for the development of new prognostic biomarkers and anti-cancer drugs in lung and esophageal cancers [9].…”
Section: Introductionmentioning
confidence: 99%
“…31, 32 Knockdown of OIP5 expression has been reported to inhibit cell growth of several cancer cell lines. 33, 34 The serine/threonine kinase Aurora-A plays a pivotal role in several mitotic events including the establishment of mitotic spindle, centrosome duplication, centrosome separation as well as maturation, chromosomal alignment, spindle assembly checkpoint, and cytokinesis. 35 CKS2 associates with cyclin-dependent kinases and has been shown to play a direct role in cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the findings as previously reported, we also predicted several novel potential chromosome aberrations, which were not found in previous array-based studies. Among them, a representative chromosome regions were located on the chromosome 15.1, which were enriched by a number of up-regulated carcinogenesis-related genes, such as OIP5 , a potential cancer therapeutic target [50], and PAK6 , a member of the p21-activated kinase (PAK) family of serine/threonine kinases, may play roles in the regulation of cell motility and in stress responses [51]. Our findings gave a deep insight into the HCC pathogenesis at the level of chromosome.…”
Section: Discussionmentioning
confidence: 99%